EFL PRE-SERVICE TEACHERS’ PERCEPTIONS AND EXPERIENCES OF ONLINE TEACHING PRACTICE - Uum Mahpudoh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract This research aims to know EFL pre-service teachers’ perceptions and experiences of online teaching practice. Due to the fact that this online teaching practice is doing for the first time, the researcher attempted to analyze their perceptions and experiences of online teaching practice during covid-19. In this study, the researcher used descriptive qualitative research. Furthermore, the participants of this research were the seventh semester which consisted of 30 students of English Department of University Islam Malang. In gathering the data, the researcher used instruments namely online questionnaire and interview. The questionnaire and interview used the Indonesian language. The questionnaires and interviews were adopted from (Nutriansi, 2015). The data was analyzed by using theory Sugiyono (2015) for questionnaire, and Enthoven et al., (2021) for interviews. Identifying the data showed that EFL pre-service teachers had a positive perception of online teaching practice in four aspects such as personal competence, pedagogical competence, professional competence, and social competence (Ramadhan et al., 2019). The results also showed that the problems found during online teaching practice program like poor infrastructure, unstable networks, ineffective delivery of online learning materials, a lack of ability in developing learning media, a lack of technology knowledge, and a lack of interaction with in-service teachers. Additionally, the EFL pre-service teachers use some strategies to solve the problems by using ICT, keeping in touch with in-service teachers, and making interesting materials. Those strategies give a positive impact on online teaching and learning classes where pre-service teachers can know students deeply and make them feel enjoy the class activities. Based on the findings, future research should choose interview participants based on their individual scores on the top three from the result of the questionnaires. For EFL pre-service teachers who achieved a lower score, they can improve their understanding of how to enhance teaching practice and minimize difficulties in online teaching practice. Keywords: EFL Pre-Service Teachers, Online Teaching Practice, Experience, Perception